STandards for Reporting Interventions in Clinical Trials Of Tuina/Massage (STRICTOTM): Extending the CONSORT statement. Issue 1 (14th March 2023) - Zhang, Xuan; Liang, Feng; Lau, Chung Tai; Chan, Jacky CP; Wang, Nana; Deng, Jiashuai; Wang, Juan; Ma, Yanfang; Zhong, Linda L. D.; Zhao, Chen; Yao, Liang; Wu, Taixiang; et al.
Abstract: Objectives: Massage is a common therapy of nonpharmacological treatments, particularly in Tuina (Chinese massage) as its most common style, detailed guidance in reporting the intervention is warranted for its evaluation and replication. Based on the CONSORT (Consolidated Standards of Reporting Trials), we aimed to develop an Extension for Tuina/Massage, namely "The STandards for Reporting Interventions in Clinical Trials Of Tuina/Massage (STRICTOTM)." Methods: A group of professional clinicians, trialists, methodologists, developers of reporting guidelines, epidemiologists, statisticians, and editors has developed this STRICTOTM checklist through a standard methodology process recommended by the EQUATOR (Enhancing the QUAlity and Transparency of Health Research) Network, including prospective registration, literature review, draft of the initial items, three rounds of the Delphi survey, consensus meeting, pilot test, and finalization of the guideline. Results: A checklist of seven items (namely Tuina/Massage rationale, details of Tuina/Massage, intervention regimen, other components of the intervention, Tuina/Massage provider background, control or comparator interventions, and precaution measures), and 16 subitems were developed. Explanations and examples (E&E) for each item are also provided. Conclusions: The working group hopes that the STRICTOTM, in conjunction with both the CONSORT statement and extension for nonpharmacologic treatment, can improve the reporting quality and transparency of Tuina/Massage clinical research.